Development of picture story learning media based on the Buayo Kuning Folklore assisted by augmented reality technology in regional literature courses - Hiasa, Fina; Supadi, Supadi; Wisman, Wisman (Universitas Ahmad Dahlan, 2024)
This development research aims to produce a product in the form of a picture story using augmented reality technology based on Bengkulu folklore with a focus on the Buayo Kuning folklore. It is hoped that the presence of folk tales transformed into regional language illustrated story discourse will attract young speakers to read and enjoy their local wisdom. The presence of augmented reality technology in picture books will provide an interactive, sophisticated and modern appearance in accordance with the interests of young speakers, namely students in regional literature courses. The method applied in this development research is R&D. Data collection on Bengkulu ethnic children's literature was carried out by interviewing, recording and noting relevant informants following standard principles of folklore collection. Apart from that, there is a product feasibility test by material experts, media experts, and user responses. The result of the validation implementation is the total average value obtained from the combined validation of material experts, media and users, namely 4.00. Based on the average score obtained, it can be concluded that the product that the researcher developed is suitable for use as an alternative learning media in increasing regional literary literacy for students based on their local wisdom.